Assessment of job satisfaction and retention among medical doctors and nurses in a developing country setting: a survey in Calabar, Nigeria - Orhungul, Ushahemba; Onugu, Mba; Udo, Victoria; Udoh, Chinenye; Omoronyia, Ogban (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, there is a rising shortage of healthcare workers, especially among doctors and nurses, potentially impairing quality of care provision. In Nigeria, this deficient workforce is further worsened by job dissatisfaction and brain drain. This study was aimed at assessing the determinants of job satisfaction and retention among medical doctors and nurses in public hospitals. Methods: Cross-sectional study design and systematic random sampling was conducted among medical doctors and nurses working in the two main public hospitals in Calabar Southern Nigeria. Data was entered and analyzed using statistical package for the social sciences (SPSS) version 25. Chi-square and independent t-test were employed as inferential statistics, with p value set at 0.05. Results: Two hundred and eighty-seven (287) subjects were studied. The mean age was 36.12±7.7 years ranging from 22 to 59 years. The overall level of job dissatisfaction was 49.5%, comprising 60.2% and 42.0% for doctors and nurses, respectively. Approximately a quarter of respondents (23.3%) were considered to be high retention risk. Younger age, male gender, having less than 10 years of employment duration, suboptimal remunerations and poor occupational environment, were associated with job dissatisfaction and higher retention risk (p<0.05). Conclusions: Approximately half of medical doctors and nurses are dissatisfied with their job, with attendant high retention risk. Improved funding of the public health sector is recommended, towards containing this challenge, within the context of worsening brain drain of skilled workers from developing to more developed countries. Further studies among private sector, non-urban settings and lower level of health facilities is recommended.